2019
DOI: 10.1021/acs.jced.8b00990
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficients of Cuprous and Cupric Ions in Electrolytes with High Concentrations of Bromide Ions

Abstract: This study examines the diffusion coefficients of cuprous and cupric ions in aqueous solutions containing 4–6 mol·dm–3 bromide ion. Under these conditions, the majority of the Cu2+ species is the complex CuBr4 –2, and the majority of Cu+ species is the complex CuBr3 –2. Diffusion coefficients were obtained for temperatures ranging from 298 to 334 K via a rotating disk electrode and the Levich relationship. Diffusion coefficients for the cuprous bromide complex were found to be between 11.9 and 19.1 × 10–6 cm2·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, it is unlikely that this error could amount to the current growth of the magnitude experienced in the measurements. The diffusion coefficients of Cu 2+ and Cu + were approximated as equal, which is not entirely true, and different values for them have been obtained for different systems, and the diffusion coefficient for Cu + is often slightly larger than that of Cu 2+ [47,48]. Therefore, the assumption of equal diffusion coefficients may have lead to some error in the simulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that this error could amount to the current growth of the magnitude experienced in the measurements. The diffusion coefficients of Cu 2+ and Cu + were approximated as equal, which is not entirely true, and different values for them have been obtained for different systems, and the diffusion coefficient for Cu + is often slightly larger than that of Cu 2+ [47,48]. Therefore, the assumption of equal diffusion coefficients may have lead to some error in the simulations.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] As a faculty member at CWRU in the 1980's, Prof. Savinell was involved in the development of H 2 -Br 2 flow batteries. [10][11][12][13] In more recent years his work expanded 14 to all-iron (Fe-Fe 3+ ), [15][16][17][18][19][20][21][22][23] all -copper 24,25 and zinc-iron 26 hybrid flow batteries, as well as to all-vanadium, [27][28][29][30][31] organic ambipolar 32 and microemulsion 33 RFBs.…”
Section: Introduction and Zinc-halogen Batteriesmentioning
confidence: 99%
“…Specifically, their solubility and diffusion coefficients are of paramount importance in these systems. Copper bromo-and chloro-complexes have been investigated and the thermodynamic and kinetics parameters evaluated from dilute and concentrated copper solutions [22][23][24][25][26][27][28][29]. Stability constants were also evaluated in dilute solutions of copper chloride complexes [25].…”
Section: Introductionmentioning
confidence: 99%
“…Stability constants were also evaluated in dilute solutions of copper chloride complexes [25]. It was found that in the presence of a high concentration of halides, Cu + and Cu 2+ form halide-complexes with increasing halide content by increasing the number of halide ligands, up to CuX 3 2− and CuX 4 2− in complexes for Cu(I) and Cu(II), respectively [25,26]. The diffusion coefficients of Cu + and Cu 2+ range from 10 −5 to 10 −6 cm 2 s −1 , with higher values for higher temperatures and for Cu + than for Cu 2+ , with a small variation for different X − concentration [26].…”
Section: Introductionmentioning
confidence: 99%